Blending Top-Down Federalism with Bottom-Up Engagement to Reduce Inequality in Ethiopia - Khan, Qaiser; Faguet, Jean-Paul; Ambel, Alemayehu (Elsevier, 2018)
Donors increasingly fund interventions to counteract inequality in developing countries, where they fear it can foment instability and undermine nation-building efforts. To succeed, aid relies on the principle of upward accountability to donors. But federalism shifts the accountability of subnational officials downward to regional and local voters. What happens when aid agencies fund anti-inequality programs in federal countries? Does federalism undermine aid? Does aid undermine federalism? Or can the political and fiscal relations that define a federal system resolve the contradiction internally? We explore this paradox via the Promotion of Basic Services program in Ethiopia, the largest donor-financed investment program in the world. Using an original panel database comprising the universe of Ethiopian woredas (districts), the study finds that horizontal (geographic) inequality decreased substantially. Donor-financed block grants to woredas increased the availability of primary education and health care services in the bottom 20% of woredas. Weaker evidence from household surveys suggests that vertical inequality across wealth groups (within woredas) also declined, implying that individuals from the poorest households benefit disproportionately from increasing access to, and utilization of, such services. The evidence suggests that by combining strong upward accountability over public investment with enhanced citizen engagement on local issues, Ethiopia’s federal system resolves the instrumental dissonance posed by aid-funded programs to combat inequality in a federation.